Ionization injection in a laser wakefield accelerator subject to a transverse magnetic field. (20th June 2018) - Zhao, Q; Weng, S M; Sheng, Z M; Chen, M; Zhang, G B; Mori, W B; Hidding, B; Jaroszynski, D A; Zhang, J
Abstract: The effect of an external transverse magnetic field on ionization injection of electrons in a laser wakefield accelerator (LWFA) is investigated by theoretical analysis and particle-in-cell simulations. On application of a few tens of Tesla magnetic field, both the electron trapping condition and the wakefield structure changes significantly such that injection occurs over a shorter distance and at an enhanced rate. Furthermore, beam loading is compensated for, as a result of the intrinsic trapezoidal-shaped longitudinal charge density profile of injected electrons. The nonlinear ionization injection and consequent compensation of beam loading lead to a reduction in the energy spread and an enhancement of both the charge and final peak energy of the electron beam from a LWFA immersed in the magnetic field.